The Mtatsminda Pantheon: a memory site and symbol of identity - Chikovani, Nino (Caucasus survey, 2021)
The paper deals with the Pantheon of Writers and Public Figures at the Mtatsminda rise in Tbilisi. The latter represents a memory site of widely recognized symbolic importance for a long time. Initiated at the end of the nineteenth century and opened in the 1920s, the Pantheon was conceived of as a symbol of collective identity of Georgia. The status of the Pantheon of Writers and Public Figures has largely defined its history in the following decades, both in the Soviet period and afterwards. The paper aims to trace the transformation of the idea of the Mtatsminda Pantheon as a symbol of Georgian identity over a century, to explain how and why the meanings assigned to the Pantheon evolved over time, thus contributing towards the formation of a collective memory – one of the essential elements of national identity. The work draws upon factual evidence and theoretical judgements presented in various pieces of research, as well as the analysis of papers reflecting different subject-specific discussions, information spread by media outlets, including popular newspapers, magazines, and official documents.